Improving the Methodology of Teaching "Applied Decorative Arts" Through Software Tools and Artificial Intelligence in Pedagogical Higher Education Institutions of Uzbekistan - Jabbarov Rustam Ravshanovich (Next Scientists International Journal EIJP, 2026)
This article investigates the possibilities of improving the methodology of teaching Applied Decorative Arts in higher education institutions through the application of modern software tools and artificial intelligence. The limitations of traditional instructional approaches are examined, and the theoretical foundations and practical pathways for integrating digital tools into the teaching process are elucidated. The results demonstrate that the use of software products and artificial intelligence significantly enhances students' creative competency, academic motivation, and skills in the digital interpretation of national ornamental patterns.